2019
DOI: 10.31557/apjcp.2019.20.10.2979
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Blood, Tissue and Serum Levels of Carcinoembryonic Antigen (CEA) Detection in Breast Cancer

Abstract: surgery (Wang et al., 2010). Reverse transcription polymerase chain reaction (RT-PCR) as a molecular technique has been used to measure tumor-specific mRNA expression. Tumor-specific mRNAs are specifically expressed and they will be markedly up regulated in tumor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In normal breast, we demonstrated that in fact a minor subset of normal luminal breast epithelial cells do express CEACAM5, and that positive cells preferably are present as part of a mature luminal compartment. While it has not been reported previously by immunohistochemistry [17,22,23,29], presence of CEACAM5 in normal breast tissue has been detected with RT-PCR [36]. Previously, we have examined CEACAM6 and found a similar correlation to a differentiation hierarchy both in normal epithelial tissue and in breast cancer [31].…”
Section: Figure 3: Pairs Of Primary Breast Cancer and Lymph Node Metamentioning
confidence: 88%
“…In normal breast, we demonstrated that in fact a minor subset of normal luminal breast epithelial cells do express CEACAM5, and that positive cells preferably are present as part of a mature luminal compartment. While it has not been reported previously by immunohistochemistry [17,22,23,29], presence of CEACAM5 in normal breast tissue has been detected with RT-PCR [36]. Previously, we have examined CEACAM6 and found a similar correlation to a differentiation hierarchy both in normal epithelial tissue and in breast cancer [31].…”
Section: Figure 3: Pairs Of Primary Breast Cancer and Lymph Node Metamentioning
confidence: 88%
“…Likewise, as far as we know, it is the first study that has assessed CEA as a target for a murine allograft model of BC. Indeed, the serum CEA level is a parameter widely used in the clinical diagnosis and prognosis of BC [37,38]. Therefore, there are many patents claiming to have developed kits or platforms based on CEA for BC diagnosis [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Besides its versatility and applicability for TNBC, MFCEA might benefit patients with different neoplasias. The anti-CEA decoration of nanoparticles may make MFCEA able to target any CEA positive malignant tumor such as breast, colorectal, ovarian, bladder, bronchial, lung, stomach and pancreatic cancers [14,37,[73][74][75][76][77][78][79][80][81], making it a promising theranostic nanodevice for management of various types of cancer and metastasis. In conclusion, the biocompatibility of MFCEA and its ability to target and to remain in CEA positive tumors make this nanomaterial a promising device for cancer management; however, further studies must be carried out to improve its performance and ensure its safety.…”
Section: Discussionmentioning
confidence: 99%
“… 10 It has clinical application in monitoring the condition of lung cancer and judging the curative effect and prognosis. 11 CYFRA21-1 is highly expressed in various types of tumor epithelial cells, and gradually released into the blood circulation with tumor cell apoptosis. 12 In recent years, research projects have found that the concentration of TuM2-PK in the peripheral blood of tumor patients has significantly increased, which can be used for early diagnosis, prognosis assessment, and therapeutic monitoring of tumors.…”
Section: Introductionmentioning
confidence: 99%